Implementation of tourism circuit concept in an android-based tourist navigation application through A* algorithm - Jonardo R. Asor; Gene Marck B. Catedrilla; Cris Q. De Leon; Sharon L. Ramos (Indonesian Journal of Electrical Engineering and Computer Science, 2021)
Circuit tourism allows for inclusive growth of tourism since it allows for multi-site visits. Normally three or more tourist attractions are linked together in a tour of the tourist’s choosing. The main objective of this study is to develop an android-based application for searching tourist spots in Los Baños, Laguna, Philippines that is also capable of recommending succeeding places to visit using A* algorithm. Upon development of the application, this paper proves that A* algorithm can be used to recommend another tourist spot by analyzing the distance of the tourist spots near the user, and the most convenient routes through which they can be reached. Based on backward and forward compatibility testing, the application is operating system friendly, since it can be used in lower versions of android. Further, it is shown in the users’ evaluation that the application is acceptable to the locals of Los Baños, Laguna, Philippines. The application also contributes to advertising other tourist spots in the said municipality, specially those who were not so popular to the tourists.